Teacher code of ethics in improving the quality of education in elementary schools - Yuniarti Yuniarti; Yunardi Kristian Zega (Perkumpulan Peneliti Pendidikan dan Pengembangan Anak, 2023)
A code of ethics in the world of education is very important, teachers who have ethics are teachers who tend to be respected. In reality today, there are many teachers who forget their identity as role models who should be examples in their daily behavior. With that, the aim of having a code of ethics for a teacher is that it can serve as a guide in behaving as a teacher, as well as changing the minds, hearts, character and feelings of the students being educated by providing examples and role models in applying the code of ethics called teacher ethics in everyday. Elementary school (SD) is the initial stage for students in experiencing education, for this reason elementary school teachers must have good ethics so that the education that students receive is good and correct initial education and with teachers implementing teacher ethics it will be much easier to improve the quality of education in schools because teacher ethics have a big influence on schools. For this reason, this research method uses descriptive qualitative research with a library approach. The results obtained include: first, mutual respect between teachers and teachers becomes an example for students in respecting each other. Second, teachers are able to prepare teaching materials on time so that the teaching and learning process becomes more organized and planned which makes students more serious about learning. Third, teachers at school are able to be responsible mentors so that students feel safe, comfortable and cared for. With this, problems that often occur in the school environment will be minimized.